Antimony-resistant PGPR mitigates Sb toxicity and accumulation in peppers by restructuring rhizosphere microorganisms - Sheng, Xiangquan; Zhu, Jianzhong; Li, Wenqian; Wan, Juan; Wu, Kangbo; Yang, Pan; Duan, Renyang; Yang, Zeliang; Bai, Jing; Zheng, Yu (Frontiers in Microbiology, 2025)
Plant growth-promoting rhizobacteria (PGPR) provide a sustainable biofertilizer strategy for remediating heavy metal-contaminated soils by enhancing plant stress resistance through rhizosphere microbiota interactions. However, the mechanisms by which PGPR modulate rhizosphere communities and plant growth under antimony (Sb) stress remain poorly understood. This study investigated the effects of inoculating Sb-tolerant Cupriavidus sp. S-8-2 in pepper (Capsicum annuum L.) cultivated under varying levels of Sb contamination (0, 500, 1,000 mg/kg), employing a combination of metagenomic profiling and physicochemical analyses. Pot experiments demonstrated that inoculation significantly enhanced plant growth and nutrient acquisition while alleviating oxidative stress in Sb-stressed plants. Crucially, it reduced Sb translocation, resulting in a 54.75% decrease in shoot Sb content, along with a 33.33% increase in leaf biomass and a 38.98% increase in root biomass under 1,000 mg/kg Sb treatment. In parallel, rhizosphere properties such as total nitrogen (TN), total phosphorus (TP), and soil organic matter (SOM) were improved, as evidenced by an 81.35% increase in acid phosphatase activity under the same Sb concentration. Microbiota analysis revealed that inoculation enriched stress-responsive bacterial phyla, such as Proteobacteria and Actinobacteria, as well as key functional genera associated with Sb tolerance (e.g., Ramlibacter) and nutrient cycling (e.g., Nitrospira), despite a decrease in alpha-diversity. Co-occurrence networks analysis indicated that inoculation significantly enhance node connectivity and mean degree in rhizosphere bacterial networks, reflecting an increase in structural complexity, especially under severe Sb stress (1,000 mg/kg). These findings demonstrate that Cupriavidus sp. S-8-2 enhances plant resistance to Sb by restructuring the rhizobacterial community and improving soil health, with reducing Sb accumulation in edible parts, thereby highlighting its potential as a biofertilizer for safe crop production in Sb-contaminated soils. For the first time, our study explored the potential of Sb-tolerant PGPR to alleviate Sb stress in pepper plants cultivated in Sb-polluted soils.